Uneasy Alliance: Conservative Catholics and the Christian Right - Bendyna, Mary E. (Sociology of religion, 2001)
Christian Right organizations in the 1990s have tried to avoid the pitfalls of the religious particularism that undermined the earlier efforts of such groups as the Moral Majority to build long lasting political coalitions. For many Christian Right leaders, conservative Catholics appear to be a particularly appealing group to reach for membership recruitment and political coalition building. Yet such leading groups as the Christian Coalition have largely experienced disappointment with such efforts.This essay presents data that offer reasons for why conservative Catholics might be willing to form into political coalitions with activists of the Christian Right but remain reluctant to join Christian Right organizations. The findings are based on a large survey of Republican party state convention delegates in Virginia. The data show that Catholic delegates hold very conservative issue positions in line with Christian Right organizations and have positive feelings toward Christian Right candidates and organizations. Yet they hold somewhat distinctive positions among Republicans on issues of the death penalty, teaching of Creationism, and the social welfare net, among others, and therefore remain reluctant to join the Christian Coalition and other such groups.